Masculine vs Feminine Personality Traits and Women's Employment Outcomes in Britain: A Field Experiment - Nick Drydakis; Katerina Sidiropoulou; Swetketu Patnaik; Sandra Selmanovic; Vasiliki Bozani (Institute of Labor Economics (IZA), 2017)
In the current study, we utilized a correspondent test to capture the way in which firms respond to women who exhibit masculine and feminine personality traits. In doing so, we minimized the potential for reverse causality bias and unobserved heterogeneities to occur. Women who exhibit masculine personality traits have a 4.3 percentage points greater likelihood of gaining access to occupations than those displaying feminine personality traits. In both male- and female-dominated occupations, women with masculine personality traits have an occupational access advantage, as compared to those exhibiting feminine personality traits. Moreover, women with masculine personality traits take up positions which offer 10 percentage points higher wages, in comparison with those displaying feminine personality traits. Furthermore, wage premiums are higher for those exhibiting masculine personality traits in male-dominated occupations, than for female-dominated positions. To the best of our knowledge, this is the first field experiment to examine the effect of masculine and feminine personality traits on entry-level pay scales. As feminine personality traits are stereotypically attributed to women, and these characteristics appear to yield fewer rewards within the market, they may offer one of many plausible explanations as to why women experience higher unemployment rates, whilst also receiving lower earnings, as compared to men.
Keywords: J16; J31; 330; masculine traits; feminine traits; occupational access; wages; field experiment